2019
DOI: 10.1038/s41467-019-12102-y
|View full text |Cite
|
Sign up to set email alerts
|

Reaction selectivity of homochiral versus heterochiral intermolecular reactions of prochiral terminal alkynes on surfaces

Abstract: Controlling selectivity between homochiral and heterochiral reaction pathways on surfaces remains a great challenge. Here, competing reactions of a prochiral alkyne on Ag(111): two-dimensional (2D) homochiral Glaser coupling and heterochiral cross-coupling with a Bergman cyclization step have been examined. We demonstrate control strategies in steering the reactions between the homochiral and heterochiral pathways by tuning the precursor substituents and the kinetic parameters, as confirmed by high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
4
25
0
Order By: Relevance
“…One particular subset of on-surface organic reactions that has attracted considerable attention are those involving alkyne functional groups . Several reactions exist that involve homocoupling to other alkynes, as well as mechanisms that include heterocoupling to different functional groups, such as cycloadditions with azides , or couplings with halogenated species. Focusing on alkyne homocoupling, there is already a wide variety of possible reaction schemes that include dehydrogenative Glaser coupling, as well as non-dehydrogenative head-to-head or head-to-tail alkyne coupling, all of which have been readily reported as occurring on coinage metal surfaces under ultrahigh vacuum. , The two former coupling motifs are difficult to discern, , and although most of these works reported Glaser coupling as dominant, the few studies performed with BR-SPM revealed Glaser coupling to be absent and the non-dehydrogenative alkyne coupling to be the most common instead. , Nevertheless, it has been recently demonstrated with BR-SPM that on-surface Glaser coupling can occur at the intramolecular level upon tip-induced manipulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One particular subset of on-surface organic reactions that has attracted considerable attention are those involving alkyne functional groups . Several reactions exist that involve homocoupling to other alkynes, as well as mechanisms that include heterocoupling to different functional groups, such as cycloadditions with azides , or couplings with halogenated species. Focusing on alkyne homocoupling, there is already a wide variety of possible reaction schemes that include dehydrogenative Glaser coupling, as well as non-dehydrogenative head-to-head or head-to-tail alkyne coupling, all of which have been readily reported as occurring on coinage metal surfaces under ultrahigh vacuum. , The two former coupling motifs are difficult to discern, , and although most of these works reported Glaser coupling as dominant, the few studies performed with BR-SPM revealed Glaser coupling to be absent and the non-dehydrogenative alkyne coupling to be the most common instead. , Nevertheless, it has been recently demonstrated with BR-SPM that on-surface Glaser coupling can occur at the intramolecular level upon tip-induced manipulation …”
Section: Introductionmentioning
confidence: 99%
“…Alkyne groups may also undergo on-surface cyclization reactions such as the Bergman cyclization. , Cycloaddition reactions, such as the [2 + 2 + 2] , and [1 + 1 + 1 + 1] types are another possible route toward generating conjugated cyclic linkages. Other varieties such as cascade-type cyclization reactions , have also been studied and allow the formation of polymers after the cyclization step.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the metal–organic coordination template effect could also greatly improve the selectivity of some on-surface covalent coupling reactions, as revealed by Xing et al . and Wang et al …”
mentioning
confidence: 99%
“…22 In Liu et al's work, the preformed molecular arrangement from the synergy of π−π, CH−π, and Br−Br bond interactions has been demonstrated to play a crucial role in the formation of highly ordered 2D porous polymers. 23 In addition, the metal−organic coordination template effect could also greatly improve the selectivity of some on-surface covalent coupling reactions, as revealed by Xing et al 24 and Wang et al 27 All of the above-mentioned examples of self-assembly confinements are positive to on-surface synthesis, by efficiently tuning the reaction pathways. Owing to the self-assembly guidance, the ideal reaction pathways dominate, although they are not the thermodynamically or kinetically favorable paths in an unrestricted reaction of free molecules on surfaces.…”
mentioning
confidence: 99%
“…The areas of the three components perfectly reflect the abundance of the three species in the organometallic wires. 31,32 The formation of the 2,1 GY MW modifies the C atoms bonded to the metal into C atoms linked to three C atoms; the resulting XPS region can now be fitted with just the two red and blue components, that substantially maintain the same positions reported for the organometallic wires. Thanks to the synthetic strategy proposed in this work, we obtained a long-range ordered, dense array of separated GY MWs with lengths that can easily reach 100 nm, as reported in Figure 2e, which shows that the polymers can cross the surface steps, and can bend from linearity by small angles, in tune with the flexibility of similar molecular wires such as PPP.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 73%